INFAQ TIDAK DAPAT DIKATEGORIKAN SEBAGAI PUNGUTAN LIAR - HASTUTI, QURRATUL ‘AINI WARA (UIN Sunan Kudus, 2016)
Infaq can not be categorized as the illegal fees, because infaq have a clear legal basis in Islamic Law and Positive Law in Indonesia, in the submission of treasure infaq, givers and receivers infaq only based on sincerity and worship to God, not because of compulsion, and infaq targeted at realize the benefit of the people, while the illegal fees, the giver and the receiver treasure oriented only on personal interests.